Thriving Seagrasses in Rocky Sandy Substrate in Tinabilan, Northwest Leyte, Philippines - Jason G. Tuang-tuang (PT FORMOSA CENDEKIA GLOBAL, 2022)
The coastline of Palompon, Leyte has endowed with rich seagrass abundance and diversity which supports the well-established Siganid industry. Baseline information on the cover and species composition were gathered using the transect-quadrat method. Results showed that there were four (4) species of seagrasses identified in the coastal area of Tinabilan, Palompon, Leyte. Cymodocea rotundata and Thalassia hemprichii were observed in all the sampling stations. The average percentage cover of seagrasses was 8.36% which revealed in poor condition. However, the poor percentage cover condition can be associated with the topography and environmental factors in the area which is observed to have been dominated with rocky-sandy substrate and high temperature which possibly affects negatively the biological processes of the seagrass species.